Prostate cancer incidence on cystoprostatectomy specimens is directly linked to age: results from a multicentre study. (11th August 2014) - Pignot, Géraldine; Salomon, Laurent; Lebacle, Cédric; Neuzillet, Yann; Lunardi, Pierre; Rischmann, Pascal; Zerbib, Marc; Champy, Cecile; Roupret, Morgan; Peyronnet, Benoit; Verhoest, Gregory; Murez, Thibault; et al.
<x xml:space="preserve">Abstract</x> Objective To assess the incidence and age‐related histopathological characteristics of incidentally diagnosed prostate cancer from specimens obtained via radical cystoprostatectomy (RCP) for muscle‐invasive bladder cancer. Patients and Methods A retrospective review of the histopathological features of 2424 male patients who underwent a RCP for bladder cancer was done at eight centres between January 1996 and June 2012. No patient had preoperative suspicion of prostate cancer. Statistical analyses were performed in different age‐related groups. Results Overall, prostate cancer was diagnosed in 518 men (21.4%). Incidences varied significantly according to age (5.2% in those aged <50 years to 30.5% in those aged >75 years, P < 0.001). Most of the prostate cancers were considered as 'non‐aggressive', that is to say organ‐confined (≤pT2) and well‐differentiated (Gleason score <7). Tumour‐Node‐Metastasis (TNM) stage and proportion with a Gleason score of ≥7 were significantly greater in older patients (P < 0.001). Apart from age, there were no preoperative predictive factors for 'non‐aggressive' prostate‐cancer status. At the end of the follow‐up, only nine patients (1.7%) had biochemical recurrence of prostate cancer, and no preoperative predictive factors were identified. Conclusion The rate of incidentally diagnosed prostate cancer from RCP specimens is ≈20%, most of them being organ‐confined and well‐differentiated. The probability of having a 'non‐aggressive' prostate cancer decreases in older men.